2020
DOI: 10.1177/1479973120922538
|View full text |Cite
|
Sign up to set email alerts
|

Validity of balance and mobility screening tests for assessing fall risk in COPD

Abstract: People with chronic obstructive pulmonary disease (COPD) have balance impairments and an increased risk of falls. The psychometric properties of short balance tests to inform fall risk assessment in COPD are unknown. Our objective was to determine the validity (concurrent, convergent, and known-groups) of short balance and mobility tests for fall risk screening. Participants with COPD aged ≥ 60 years attended a single assessment. Correlation coefficients described the relationships between the Brief Balance Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
16
1
Order By: Relevance
“…The TUG test has been reported to identify patients at risk for falls due to cognitive impairment [48]. However, in disagreement with other studies [47,49,50,51], our multivariable analysis revealed that the TUG tests were not independently associated with the risk of falls in older adults living in the UAE. Herman et al (2009) stated that the DGI is a very important test in predicting the risk of fall for older adults as it measures the gait instability and evaluates not only usual walking, but also walking during more challenging tasks as a demand of changing the position during walking [52].…”
Section: Discussioncontrasting
confidence: 95%
“…The TUG test has been reported to identify patients at risk for falls due to cognitive impairment [48]. However, in disagreement with other studies [47,49,50,51], our multivariable analysis revealed that the TUG tests were not independently associated with the risk of falls in older adults living in the UAE. Herman et al (2009) stated that the DGI is a very important test in predicting the risk of fall for older adults as it measures the gait instability and evaluates not only usual walking, but also walking during more challenging tasks as a demand of changing the position during walking [52].…”
Section: Discussioncontrasting
confidence: 95%
“…Minimal floor effects were found in patients severe-COVID and CLD, similar to previous findings in patients with COPD at 1 month after hospital discharge. 39 However, 14% of critical-COVID survivors were unable to perform the TUG or DT-TUG 1-month post discharge. Additionally, the MDC values reported here are of substantial value to clinical determinates of DT performance across time, or future intervention studies aiming to develop targeted rehabilitation strategies to address DT deficits in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The SLS was performed three times with a pause between repetitions, and the best value was recorded [ 39 ]. The SLS test is a valid test in COPD that can indicate fall risk in COPD [ 40 ]. Values <30 s with open eyes indicated impaired balance in the general population > 60 years old [ 35 ].…”
Section: Methodsmentioning
confidence: 99%